(untitled) (Proceedings of Voronezh State University. Series: Geology, 2020)
Introduction: The Tashly-Tau massif is a small olivine-hornblende gabbro stock that represents the earliest manifestations of the products of differentiated magmatism in the Khudolaz complex. The complex has a complicated geological structure. Therefore, the detailed petrological and geochemical studies of individual massifs using numerical simulation of crystallisation parameters make it possible to determine the formation features of the Khudolaz complex as a whole. The aim of the study is to reconstruct the paleogenesis of the gabbroids of the Tashly-Tau massif, which is also important because of the massif’s sulphide Cu-Ni mineralisation. Methodology: Rock forming minerals of the gabbroids were studied using an optical microscope Axioskop 40 and a scanning electron microscope Tescan Mira 3. The chemical composition of the rocks was determined using the X-ray fluorescence analysis and inductively coupled plasma mass spectrometry. The isotopic composition of Sr and Nd was studied using thermal ionisation spectrometry. To model the petrogenesis, numerical COMAGMAT modelling and the method of geochemical thermometry were used. Results and discussion: The petrological and geochemical study of the rocks in the Tashly-Tau massif was carried out. It showed an extensive presence of the hornblende, titanous magnesiohastingsite ( 50 wt. %). The gabbroids are characterised by their relative enrichment in large-ion elements (Cs, Rb, Sr, Ba) and depletion in high field strength elements (Nb, Ta, Zr, Hf, REE). Based on the geochemical data, it was concluded that the magmatic melt was poorly differentiated. The numerical simulation showed that the rocks were formed from magma, consisting of 20 wt. % olivine phenocrysts (Fo 76) and water-saturated basalt melt ( 1.7 wt. % H2O). The melt is characterised by high alumina and iron content and moderate magnesium content. The Sr-Nd isotopic composition of the rocks refers to little crustal contamination of the primitive melt. They are characterised by high positive values of εNd(Т) (+5.2...+10.3) and a low content of radiogenic strontium. A mantle reservoir of the PREMA type could be a source of the parent melt. Conclusions: The obtained results are important for understanding the formation nature of the complicatedly differentiated Khudolaz complex, specialised in sulphide mineralisation. This complex is unique to the Urals. It was shown that the use of numerical simulation of water-saturated basalt systems can be quite effective until the crystallisation of hydroxyl-containing rock forming minerals (the hornblende).